»Sprache der Nähe – Sprache der Distanz« – aus linguistischer Perspektive. Wissenschaftshistorische Einordnung. - Hennig, Mathilde (Mitteilungen des Deutschen Germanistenverbandes, 2019)
The article offers information on the language of proximity. Topics discussed include the language of distance from a linguistic perspective, and history of the science of language classification. Also being discussed are the two novelists, Peter Koch and Wulf Oesterreicher who developed the models of language of proximity and language of distance.